Environmental news in regional press: analysis of the evolution of issues, focus and sources - Portilla, Idoia; González, Hildegart (Estudios sobre el Mensaje Periodístico, 2015)
The first purpose of this paper is analyzing issues, priority focus and sources of reference in environmental news published in regional newspapers Diario de Navarra and Diario de Noticias. The second purpose is studying the evolution of these three elements, possible trends and factors that can affect it. The news were registered by the Centro de Recursos Ambientales de Navarra (CRANA). The period of analysis is January 1, 2004 to December 31, 2012 and the sample is configured by 2,125 news. The information from the quantitative content analysis is complemented by in depth interviews to people in charge of the CRANA and a qualitative analysis of the content of part of the sample.
Keywords: Environment; issues; focus; sources.